Nociception modulation by supraspinal group III metabotropic glutamate receptors. Issue 4 (22nd February 2017) - Palazzo, Enza; Marabese, Ida; Luongo, Livio; Guida, Francesca; de Novellis, Vito; Maione, Sabatino
Abstract: The modulatory actions of glutamate, the main excitatory neurotransmitter in the central nervous system (CNS), are exerted through the activation of metabotropic glutamate receptors (mGluRs). Of the eight known mGluRs (mGluR1–8), group III mGluRs (mGluR4, mGluR6, mGluR7, and mGluR8) are less understood because of the lack of selective ligands. Except for mGluR6, group III mGluRs are widely distributed throughout the CNS. They are mainly located on presynaptic terminals where they inhibit neurotransmitter release at glutamatergic and γ‐aminobutyric acid (GABA)ergic synapses. Their location at certain synapses is considered critical for normal CNS function, which makes them potential targets in neurological and psychiatric treatments. Novel ligands that are selective for group III mGluR subtypes have recently been developed. These compounds, which mainly target allosteric sites and act as positive or negative allosteric modulators (PAMs or NAMs) of glutamate transmission, are contributing to the understanding of the functional roles of group III mGluRs in a number of pathological conditions, such as epilepsy, anxiety, neurodegenerative diseases, and chronic pain. Moreover, the presence of group III mGluRs throughout the entire pain neuraxis and particularly in the descending system suggests that these endogenous substrates that extend from the cortex to the first spinal synapse are candidates for pain control. Recent data on chronic pain alleviation by group III mGluR ligands encourage further studies as pathological pain is one of the most troublesome diseases because of the current lack of satisfactory therapy. This review summarizes recent studies on group III mGluRs in animal models of chronic pain, which evidence an opposite modulation of mGluR7 and mGluR8 on pain responses and their capability to affect pain responses only in pathological states. This article is part of the special article series "Pain" . Abstract : The modulatory actions of glutamate, the main excitatory neurotransmitter in the central nervous system (CNS), are exerted through the activation of metabotropic glutamate receptors (mGluRs). Novel ligands that are selective for group III mGluR subtypes have recently been developed. These compounds, which mainly target allosteric sites and act as positive or negative allosteric modulators (PAMs or NAMs) of glutamate transmission, contribute to the understanding of the functional roles of group III mGluRs in a number of pathological conditions, such as epilepsy, anxiety, neurodegenerative diseases, and chronic pain. This review summarizes recent studies on group III mGluRs in animal models of chronic pain which evidenced an opposite modulation of mGluR7 and mGluR8 on pain responses and their capability to affect pain responses only in pathological states. This article is part of the special article series "Pain" .